2012
DOI: 10.1186/1475-2875-11-255
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profiles of artesunate following multiple intravenous doses of 2, 4, and 8 mg/kg in healthy volunteers: Phase 1b study

Abstract: BackgroundSevere malaria results in over a million deaths every year, most of them in children aged less than five years and living in sub-Saharan Africa. Injectable artesunate (AS) was recommended as initial treatment for severe malaria by WHO in 2006. The Walter Reed Army Institute of Research (WRAIR) has been developing a novel good manufacturing practice (GMP) injection of AS, which was approved by the US FDA for investigational drug use and distribution by the CDC.MethodsTolerability and pharmacokinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
(41 reference statements)
3
28
0
Order By: Relevance
“…We have shown that artesunate inhibits the replication of JCPyV in COS-7 cells with an EC 50 of 2.9 M, a concentration that can be achieved in plasma (60)(61)(62). However, to be eligible for therapeutic treatment for PML, artesunate also needs to cross the blood-brain barrier and enter the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that artesunate inhibits the replication of JCPyV in COS-7 cells with an EC 50 of 2.9 M, a concentration that can be achieved in plasma (60)(61)(62). However, to be eligible for therapeutic treatment for PML, artesunate also needs to cross the blood-brain barrier and enter the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…However, to inhibit the replication of BKV in RPTECs by 50% (i.e., the EC 50 ), a concentration of 4.2 M (1.6 g/ml) artesunate was needed, and it is still unclear if this concentration can be attained in kidney epithelial cells in vivo. Following intravenous administration of artesunate in healthy volunteers, plasma concentrations up to 217 M (83.34 g/ml) have been described (29,53,54), indicating that the EC 50 could at least be achieved in the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…ART was able to inhibit viability in clinically achievable concentrations [10] and in a time-dependent manner in IL-6-independent and -dependent MM cell lines (Suppl. Table S1A; Fig.…”
Section: Resultsmentioning
confidence: 99%